Socjologiczne rozumienie wartości w aspekcie relacjonistycznym - Szymczyk, Jan (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2019)
The aim of the text is to present, from the subject-object (psychosocial) perspective, the ontological status of values, and, secondly, to explicate the merits of applying this perspective (the object of the analysis is the correlation between values and interests, and between axiological categories and neighbourly ties of the Poles). The relationist perspective, applied to the axiological (values) and pragmatic (interests) spheres, allows a more accurate (in an epistemological understanding of the term) perception of the analysed subjects or the phenomena of social life (e.g. neighbourly relations). What is more, from the psychosocial perspective, analysing values and interests makes it possible to describe their significance in the processes of social integration, their functioning as motivators and regulators of human behaviour, and their functioning as the so-called mask or façade (values are merely ritualistic forms that obscure true motives behind actions or choices).